Tindak Tutur Representatif pada Channel YouTube Diklat Online tentang Perancangan Pembelajaran Mendalam - Azi Aurahman Elegan; Ezra Malvino Putra Alwi; Haris Budisetiawan; Muhammad Rolanda Hendrakusuma; Marta Alfiana Damayanti; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Universitas Palangka Raya, 2026)
This study aims to describe representative speech acts in a video with the theme of in-depth learning design on the Diklat Online YouTube Channel. The background of this study is rooted in the important role of language in social interaction and the importance of speech acts as one aspect in pragmatic studies. In the realm of digital media, people see YouTube as the right platform to analyze speech acts because it is able to facilitate interactions between speakers and interlocutors through its videos. This study uses a qualitative descriptive method with the main data sources in the form of three podcast videos from the Diklat Online channel, August 2025 edition. Data were obtained through listening and note-taking techniques, then analyzed using the pragmatic equivalent method to classify the forms of representative speech acts. The results of the study found 33 representative speech act data divided into nine categories, namely stating (9), suggesting (3), demanding (3), showing (2), informing (8), mentioning (3), explaining (2), speculating (1), and giving examples (2). Of all, the speech act